IL‐33/ST2 receptor‐dependent signaling in the development of pulmonary hypertension in Sugen/hypoxia mice. Issue 3 (12th February 2022) - Indralingam, Cynthia S.; Gutierrez‐Gonzalez, Alma K.; Johns, Scott C.; Tsui, Tzuhan; Cannon, Daniel T.; Fuster, Mark M.; Bigby, Timothy D.; Jennings, Patricia A.; Breen, Ellen C.
Abstract: Pulmonary arterial hypertension (PAH) is associated with significant morbidity and mortality. PAH is characterized by pulmonary artery remodeling, elevated right ventricular pressure (RVP) and, ultimately, cardiac failure. Pulmonary endothelial cells can sense danger or damage caused by mechanical injury or pathogens through alarmin cytokines. These cytokines can signal proliferation to restore barrier integrity or aberrant hyperproliferation and remodeling. We hypothesized that IL‐33 signals pulmonary artery endothelial cells to proliferate under hypertensive conditions during the remodeling response and rise in RVP. To test this hypothesis, pulmonary hypertension (PH) was induced in C57Bl/6J, IL‐33 receptor gene deleted (ST2 −/− ) and MYD88 gene deleted (MYD88 −/− ) mice by exposure to 10% O2 and SU5416 injections (SUHX). RVP, arterial wall thickness, endothelial cell proliferation and IL‐33 levels and signaling were evaluated. In response to SUHX. RVP increased in C57Bl/6J mice in response to SUHX (49% male and 70% female; p < 0.0001) and this SUHX response was attenuated in ST2 −/− mice (29% male p = 0.003; 30% female p = 0.001) and absent in MYD88 −/− mice. Wall thickness was increased in SUHX C57Bl/6J mice ( p = 0.005), but not in ST2 −/− or MYD88 −/− mice. Proliferating cells were detected in C57Bl/6J mice by flow cytometry (CD31 + /BrDU + ; p = 0.02) and immunofluorescence methods (Ki‐67+). IL‐33 was increased by SUHX ( p = 0.03) but a genotype effect was not observed ( p = 0.76). We observed that in hPAECs, IL‐33 expression is regulated by both IL‐33 and DLL4. These data suggest IL‐33/ST2 signaling is essential for the endothelial cell proliferative response in PH. Abstract : The IL‐33/ST2 pathway is essential for the early endothelial cell proliferative response in Sugen/hypoxia‐induced pulmonary hypertension that leads to remodeling of the small resistance pulmonary arteries. The intracellular toll‐like receptor adaptor protein, MYD88, synergizes with the IL‐33/ST2 receptor complex to regulate right ventricle pressure and right ventricle contractility and remodeling.